PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR FISIKA SISWA - Ulliyah Trisna Widayati; Trapsilo Prihandono; Firdha Kusuma Ayu Anggraeni; Yusrita Yusrita (Universitas Jember, 2023)
Physics subjects are not liked by student because it have a high level ofdifficulty. The impact is that student learning outcomes in physics subjects aregenerally low. The solution is an application of a learning model with picture mediaor picture and picture. This study aims to improve a student learning outcomes, aswell as analyze student respons to the picture and picture learning model applied. Thisresearch is an experimental research with a posttest-only control design. The dataanalysis technique of this study is to use the normality test and T-Test. The resultsthrough the Mann Whitney U-Test is 0.000<0.05 which indicated that there was asignificant difference in post-test results. While the student response obtained a 85%and get a “very positif” category.Key words : Learning model, Learning Outcomes, Picture and Picture